2007
DOI: 10.1007/s00204-007-0187-4
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China

Abstract: A total of 2,402 cases of arsenic-related skin lesions (as of 2002) in a few villages of China's Southwest Guizhou Autonomous Prefecture represent a unique case of endemic arseniasis related with indoor combustion of high arsenic coal. A significant difference of skin lesion prevalence was observed between two clans of different ethnicities (Hmong and Han) in one of the hyperendemic villages in this prefecture. This study was focused on a possible involvement of GST T1 and M1 polymorphisms in risk modulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A similar observation was reported by Wang et al [12], in which there are interindividual differences in excretion profiles and the relative concentrations of major arsenic species in urine among four Chinese APL patients undergoing ATO treatment. It is significant to note that genetic polymorphisms in arsenic metabolism genes, such as human arsenic methyltransferase (AS3MT) gene and glutathione S-transferase gene, are considered to be related to interindividual variation in the arsenic metabolism [31-33]. Collectively, continuous efforts to understand the differences in arsenic metabolism and the relationship between these genetic polymorphisms and arsenic metabolism among patients are definitely useful for providing an effective treatment protocol of ATO for individual APL patients, ultimately contribute to reduction of its side effects.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported by Wang et al [12], in which there are interindividual differences in excretion profiles and the relative concentrations of major arsenic species in urine among four Chinese APL patients undergoing ATO treatment. It is significant to note that genetic polymorphisms in arsenic metabolism genes, such as human arsenic methyltransferase (AS3MT) gene and glutathione S-transferase gene, are considered to be related to interindividual variation in the arsenic metabolism [31-33]. Collectively, continuous efforts to understand the differences in arsenic metabolism and the relationship between these genetic polymorphisms and arsenic metabolism among patients are definitely useful for providing an effective treatment protocol of ATO for individual APL patients, ultimately contribute to reduction of its side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Of these proposed key events, experimental evidence suggests sustained oxidative stress production may play an especially important role in As‐mediated carcinogenesis in the skin [reviewed in [65]]. Mutations in oxidative stress response genes are positively correlated with As‐mediated skin disease development in chronically exposed populations [66–69], and ROS‐associated DNA lesions [i.e., 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG)] are significantly associated with As‐related human skin tumors [70, 71]. The global gene transcription profiles of human hyperkeratoses (HKs), which are benign, potentially premalignant lesions associated with chronic iAs exposure [72, 73], reveal that the vast majority of most significantly altered functions (apoptosis, cell‐cycle regulation, proliferation, cellular differentiation) and pathways (e.g., MAPKs, Wnt/β‐catenin, calcium signaling, NF‐κB) in HKs compared to normal skin can be altered by oxidative stress [74–77].…”
Section: Discussionmentioning
confidence: 99%
“…For decades, the total As concentration in the drinking water sources in this village has never been detected to exceed the level the Chinese National Criteria requires (\0.05 mg/l; Liu et al 2002;An et al 2007;Lin et al 2006Lin et al , 2007. Water samples collected from all 4 drinking water sources in this village during this study showed As concentrations within the range of 0.014-0.025 mg/l (0.0181 ± 0.0049 mg/l; Lin et al 2006).…”
Section: Discussionmentioning
confidence: 98%